Effects of COVID-19 Infection Control Measures on Appointment Cancelation in an Italian Outpatient Memory Clinic - Spalletta, Gianfranco; Porcari, Desirée Estela; Banaj, Nerisa; Ciullo, Valentina; Palmer, Katie (Frontiers in Psychiatry, 2020)
Background: In the first wave of the COVID-19 pandemic in 2020, many countries made changes to the routine management of patients with non-communicable diseases, including neurocognitive disorders. Therefore, many “so-called” non-urgent elective procedures and outpatient appointments have been cancelled or postponed, possibly impacting negatively on health and wellbeing of patients in the short- and long-term. Aim: Here, we aimed at describing the number and type of outpatient appointments cancelled as a result of government’s restrictive measures in our memory clinic. Methods: The scheduled appointments at the memory clinic of the Santa Lucia Hospital Foundation IRCCS, Rome, Italy, are recorded in a comprehensive dataset under strict administrative control. Here, we compared the number of appointments (first-time and follow-up) that were cancelled from January to April 2020 with those of the corresponding months in 2019. Results: We observed a substantial decrease in appointments during 2020. The majority of scheduled appointments were follow-up, and about a quarter were first-time appointments. We estimated that 66.7 and 77.4% of patients missed out their first and follow-up appointments respectively in our memory clinic due to government's restrictive measures. Conclusions: A large number of patients with neurocognitive disorders missed crucial follow-up appointments due to government’s restrictive measures, and many experienced a delay in initial diagnosis and initiation of treatment. This has had relevant impact on their treatment and consequently has (is still having and potentially will have) an increase on the healthcare service burden of reopened clinics. Furthermore, as a second wave of COVID-19 affects Europe, and with winter approaching, it is a compelling priority to ensure easy and rapid access to appropriate assessment, care and treatment in the event of a new outbreak and potential subsequent lockdowns, with particular attention to the development of specific healthcare technologies customized to older persons with cognitive impairment.